A NOVEL METHOD FOR ISOLATION AND TRILINEAGE DIFFERENTIATION OF RAT BONE MARROW DERIVED MESENCHYMAL STEM CELLS - D, SANKARI; P, THANGARAJU; D, ALWIN; KANNAN P, THAMARAI (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Goal of this study is to find a simple method for isolation, colony formation and Trilineage differentiation of Mesenchymal stem cells from bone marrow of Wistar Rat. Adherent capacity, morphology, trilineage differentiation and colony formation of bone marrow mesenchymal stem cells were studied in low glucose, high glucose Dulbecco modified eagle medium with various concentration of fetal bovine serum. Methods: Mesenchymal stem cells were isolated from bone marrow of Wistar rat by Ficoll (sigma) density gradient centrifugation with plastic adherence method. Bone marrow was collected from femur and Tibia of 6-weeks-old Wistar rat; Bone marrow was cultured in Dulbecco's modified Eagles's medium (DMEM) with low glucose, high glucose supplement (Invitrogen) and 10%, 15% of fetal bovine serum (FBS) at the density of 1 Ã— 10 6 , incubated at 37Â°C in 5% of CO ; adherent capacity, colony formation were studied. Differentiation of bone marrow mesenchymal stem cells (BMMSCs) was monitored under suitable differentiation medium. The cells were refeed every 3-4 days and passaged when the cells reached 80-90% confluences. 2 Result: BMMSCs were adhered in tissue culture flask at 24 hrs, 48 hrs in high glucose and low glucose DMEM with 10% of FBS, respectively. Colony formation was faster in high glucose and low glucose DMEM with 15% of FBS compared to high glucose and low glucose DMEM with10% FBS. Morphological changes were observed in BMMSCs high glucose, low glucose DMEM with 10% FBS, but no changes were found in the differentiation of BMMSCs in high glucose, low glucose DMEM. Differentiation of BMMSCs was nourishing in third passage cells. Conclusion: High glucose DMEM with 10% FBS is a good supplement for adherence of cells whereas high glucose, low glucose DMEM with 15% FBS can be utilized for rapid Colony formation. Third passage BMMSCs is fruitful for differentiation of BMMSCs. Keywords: Wistar rat, Bone marrow, Mesenchymal stem cells, Adherent capacity, Colony formation, Differentiation, Osteoblast, Chondrocytes, Adipocytes.